Alternative of troubleshooting inclusive education in kindergarten - HARFIANI, R.; AKRIM, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study was aimed to provide an alternative to troubleshooting the implementation of inclusive education at the Kindergarten. The study is a qualitative research, with a case study approach, in RA. An-Nahl, Jakarta. The data collection techniques used in this study were observation, interviews, focus group discussions, and documentation which is then analyzed descriptively with an interactive analysis model. The results obtained were five common problems encountered in the implementation of inclusive education in kindergarten and to overcome these problems RA. An-Nahl carried out efforts.RESUMEN Este estudio tuvo como objetivo proporcionar una alternativa para solucionar problemas de implementación de la educación inclusiva en el jardín de infantes. El estudio es una investigación cualitativa, con un enfoque de estudio de caso, en RA.An-Nahl, Yakarta. Las técnicas de recolección de datos utilizadas en este estudio fueron observación, entrevistas, discusiones de grupos focales y documentación que luego se analizan descriptivamente con un modelo de análisis interactivo. Los resultados obtenidos fueron cinco problemas comunes encontrados en la implementación de la educación inclusiva en el jardín de infantes y para superar estos problemas RA. An-Nahl llevó a cabo esfuerzos.